2022
DOI: 10.1101/2022.01.26.477938
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The IMD and JNK pathways drive the functional integration of the immune and circulatory systems of mosquitoes

Abstract: The immune and circulatory systems of animals are functionally integrated. In mammals, the spleen and lymph nodes filter and destroy microbes circulating in the blood and lymph, respectively. In insects, immune cells that surround the heart valves (ostia), called periostial hemocytes, destroy pathogens in the areas of the body that experience the swiftest hemolymph (blood) flow. An infection recruits additional periostial hemocytes, amplifying heart-associated immune responses. Although the structural mechanic… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 116 publications
0
6
0
Order By: Relevance
“…The genome of D. melanogaster encodes one transglutaminase, and it is a negative regulator of the IMD pathway [9,10]. In mosquitoes, TGase3 is a negative regulator of periostial hemocyte aggregation [19], and because the IMD pathway is a positive regulator of periostial hemocyte aggregation [26], we hypothesized that TGase3 impacts periostial hemocyte aggregation by inhibiting the IMD pathway. The IMD pathway produces an array of antimicrobial peptides [52][53][54], and therefore, removing an inhibitor of the IMD pathway may increase antimicrobial peptide production.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The genome of D. melanogaster encodes one transglutaminase, and it is a negative regulator of the IMD pathway [9,10]. In mosquitoes, TGase3 is a negative regulator of periostial hemocyte aggregation [19], and because the IMD pathway is a positive regulator of periostial hemocyte aggregation [26], we hypothesized that TGase3 impacts periostial hemocyte aggregation by inhibiting the IMD pathway. The IMD pathway produces an array of antimicrobial peptides [52][53][54], and therefore, removing an inhibitor of the IMD pathway may increase antimicrobial peptide production.…”
Section: Discussionmentioning
confidence: 99%
“…Members of the thioester containing protein family (TEP) and nimrod protein family (NIM) influence periostial hemocyte aggregation [ 24 , 25 ]. Moreover, the IMD pathway and the interlinked JNK pathway—as tested via the RNAi-based silencing of the positive regulators rel2 , JNK1 and JNK3 , and the negative regulators caspar and puckered —drive periostial hemocyte aggregation [ 26 ]. An RNAseq analysis in that same study identified transglutaminases as being more highly expressed in the heart containing periostial hemocytes than in other tissues [ 26 ], and follow-up experiments confirmed that TGase3 —but not TGase1 or TGase2 —is a negative regulator of periostial hemocyte aggregation during the early stages of infection, presumably by inhibiting the IMD pathway [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The datasets generated and analysed during the current study are available in an accompanying electronic supplementary material dataset file [112].…”
Section: Data Accessibilitymentioning
confidence: 99%
“…The gene encoding this protein is also upregulated in periosteal hemocytes of An. gambiae after a bacterial infection [ 86 ]. Even though this pathway plays important roles in both hemocyte biology and general antiviral responses, studies connecting these two areas are lacking.…”
Section: Antiviral Immune Pathway In Hemocytesmentioning
confidence: 99%
“…gambiae [ 93 ]. In addition, the IMD and JNK pathways regulate periosteal aggregation, phagocytosis, and melanization associated with hemocytes, most probably by the regulation of TEP expression [ 86 ]. Recently, it was reported that in An.…”
Section: Antiviral Immune Pathway In Hemocytesmentioning
confidence: 99%